Formation of a system of internal financial control over ATP activities : monograph - Bocharova, Nadezhda; Kryvoruchko, Oksana; Shynkarenko, Vladimir (Siencie Scripts, 2020)
The monograph explores theoretical and practical aspects of forming an effective system of internal financial control within automobile transport enterprises (ATPs). Emphasis is placed on the development of methodological approaches to the organization, implementation, and improvement of control procedures tailored to the specific characteristics of ATP activities. The study analyzes the influence of internal control mechanisms on financial discipline, resource optimization, and the overall efficiency of enterprise management. Particular attention is given to risk-oriented control models and the integration of modern digital tools in control processes. The proposed system aims to enhance transparency, accountability, and economic sustainability in ATP operations.
Keywords: internal financial control; automobile transport enterprises; control system; financial discipline; risk management; control procedures; digital tools; economic sustainability; resource optimization